Research on Institutional Mechanisms and Policy Systems for Green Smart Energy Transformation on Islands Under Zero-Carbon Goals: A Case Study of Dachen Island, Taizhou - Wang, Shuyong; Wang, Fangshi; Dong, Ruicheng; Qian, Zhenxiao; He, Haijie; Hong, Jie; Zhao, Guogang; Ding, Qin (Journal of Global Economy, Business and Finance, 2026)
Against the backdrop of global carbon neutrality and carbon peaking goals, islands as unique geographical units face systemic challenges in their energy transition. This study aims to construct a systematic theoretical framework and design specific transition pathways using the “Zero-Carbon Smart Island” initiative on Dachen Island, Taizhou, Zhejiang Province as an empirical case. This approach seeks to overcome institutional and systemic bottlenecks in its energy transition and provide insights for similar islands. The study employs a combined approach of case analysis and theoretical construction. First, it thoroughly examines the practical challenges facing Dacheng Island’s energy transition across three dimensions: the power system, clean energy development and utilization, and policy support. Building on this analysis, it proposes and argues for a “trinity” synergistic theoretical framework: “Power System Reform – Innovation in Clean Energy Development and Utilization Mechanisms – Construction of an Energy Policy Support System.” The study reveals that Dacheng Island’s transition challenges stem from the failure of “technology-market-policy” coordination. Consequently, three core pathways are designed: In power system reform, establish a market system featuring “high-efficiency island-wide circulation + flexible external integration,” including cultivating third-party electricity sales markets, innovating cross-sea green electricity trading, and implementing island-specific electricity pricing. For clean energy development and utilization, establishing a “distributed-as-the-mainstay, centralized-as-the-supplement” development model, and constructing an integrated smart consumption mechanism for “generation-grid-load-storage” alongside multi-scenario collaborative utilization. Regarding policy support, proposing a targeted policy toolkit centered on differentiated subsidies, energy storage industry support, renewable energy consumption responsibility quotas, and regional coordination mechanisms.